Interventions to change purchasing behaviour in supermarkets: a systematic review and intervention content analysis. Issue 2 (3rd April 2022) - Golding, Sarah E.; Bondaronek, Paulina; Bunten, Amanda K.; Porter, Lucy; Maynard, Vera; Rennie, Debi; Durlik, Caroline; Sallis, Anna; Chadborn, Tim
ABSTRACT: This systematic review and intervention content analysis used behavioural science frameworks to characterise content and function of interventions targeting supermarket shoppers' purchasing behaviour, and explore if coherence between content and function was linked to intervention effectiveness. Study eligibility: in-store interventions (physical supermarkets) with control conditions, targeting objectively measured food and/or non-alcoholic drink purchases, published in English (no date restrictions). Eleven electronic databases were searched; reference lists of systematic reviews were hand-searched. Methodological quality was assessed using the GATE checklist. A content analysis was performed to characterise intervention content and function, and theoretical coherence between these, using the Behaviour Change Wheel, Behaviour Change Techniques Taxonomy, and Typology of Interventions in Proximal Physical Micro-Environments (TIPPME). Forty-six articles (49 interventions) met inclusion criteria; 26 articles (32 interventions) were included in the content analysis. Twenty behaviour change techniques (BCTs), and four TIPPME intervention types were identified; three BCTs ('Prompts/cues', 'Material incentive', and 'Material reward') were more common in effective interventions. Nineteen interventions solely employed theoretically appropriate BCTs. Theoretical coherence between BCTs and intervention functions was more common in effective interventions. Effective interventions included price promotions and/or in-store merchandising. Future research should explore the effect of specific BCTs using factorial study designs. PROSPERO Registration: CRD42017071065.